Effect of drying air temperature on the drying characteristics and quality aspects of black ginger. (May 2022) - Muthukumar, P.; Lakshmi, D.V.N.; Koch, Puja; Gupta, Mukesh; Srinivasan, G.
Abstract: This study focuses on investigating the effect of drying temperature on drying characteristics and quality aspects of black ginger dried in an electric dryer. The effect of inlet drying air temperature (40 °C–80 °C) on the drying time and drying rate of black ginger were investigated. It was observed that the drying time of black ginger was reduced by 64.2% when the drying temperature was increased to 80 °C from 40 °C. The experimental moisture ratio obtained at different drying air temperatures were compared with various thin layer drying models available in the literature. It was observed that moisture ratio predicted from Midilli and Kucuk model showed good fit with experimental drying curves at drying air temperature between 40 °C and 50 °C. The Two term model showed good fit at 60 °C and Diffusion approach model suited between 70 °C and 80 °C. It was observed that the selection of thin layer models was dependent on the inlet drying air temperature. The effective diffusivity of black ginger at 80 °C was 2.13 × 10 −9  m 2  s −1 . Quality analyses of the samples were carried out in terms of total phenolic content (TPC) and antioxidant (AA) values. Maximum values of TPC (13.58 mg GAE/g of sample) and AA (81.06%) were reported at 60 °C. Hence, a trade-off between drying time and product quality is required in selecting the drying air temperature. Graphical abstract: Image 1 Highlights: Experimental study on drying characteristics of black ginger in an electric dryer Effect of drying air temperature on drying kinetics and quality are studied. Effect of drying air temperature on various thin layer models are highlighted. Increasing drying air temperature (60 °C–80 °C) reduces TPC (19%) and AA (10.5%) values. Trade-off between drying time and product quality is needed for better drying.